Heavy Metals in Urban and Rural Indoor Dust in Plateau Homes: Levels, Sources, and Health Risks - Weiying Hou; Ruijing Hu; Zhanpeng Cui; Jinze Wang; Jie Sun; Bingyan Zhang; Xiaoyu Han; Yuanchen Chen; Yong Zhang; Dong Yang; Wei Du (Aerosol Science and Engineering, 2026)

Global Warming Amplifies Nitrogen Over Phosphorus Limitation in Aquatic Ecosystems: A Multi‐Trophic Meta‐Analysis - Misha Zhong; Ping Xie; Yuhao Feng; Wenxuan Han; Enzai Du; Di Tian; Ruijing Ma; Yuwei Wang; Zengliang Jian; Jianfeng Chen; Qingyang Rao; Shangsheng Sun; et al. (Global Change Biology, 2026)
Nitrogen (N) and phosphorus (P) availability fundamentally regulate the structure and function of aquatic ecosystems. While global‐scale patterns of relative nutrient limitation have been increasingly documented, their responses to climate warming remain poorly quantified. To address this, we integrated a global meta‐analysis of nutrient enrichment experiments (spanning 510 sites and multiple trophic levels) with large‐scale datasets of water chemistry from 3403 lakes and 13,032 marine sites. Meta‐analysis showed that primary producers have the strongest responses to nutrient enrichment, especially NP co‐addition, with effects attenuating at higher trophic levels. Increasing temperature amplifies the response of primary producers to nutrient enrichment, but not for consumers, indicating that warming disrupts energy flow to higher trophic levels. Furthermore, relative N limitation of primary producers intensifies with increasing temperature and decreasing latitude in both freshwater and marine ecosystems. Global field observation of water chemistry supports such a pattern as water N:P mass ratios decrease with increasing temperature across lake and marine ecosystems. Our findings provide robust empirical evidence that the relative nutrient limitation of primary producers exhibits a strong latitudinal gradient and climate warming could fundamentally enhance nitrogen over phosphorus limitation in aquatic ecosystems, which have critical implications for ecosystem functioning and management in a warmer world.

A robust system for somatic embryogenesis and shoot organogenesis in Begonia grandis subsp. sinensis (A. DC.) Irmsch and genetic fidelity assessment of the regenerants - Feimin Ma; Zhengli Shan; Haonan Su; Ruijing Han; Wenjing Zhou; Mu Ze; Ming Dong; Qinggui Wu; Lijuan Zou (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Characteristics and Impact Mechanisms of Spatiotemporal Patterns of Carbon Emissions in China’s Urban Agglomerations - Qingxi Shen; Yujie Zhu; Zerui Han; Yifan Deng; Ruijing Wen (Chinese Geographical Science, 2025)

Clean water and energy co-generation via alternative renewables - Xiaochao Fan; Bushra Shakoor; Han Yusen; Shi Ruijing; Yang Mingtao; Li Ziqiang; Naila Arshad; Uzma Ghazanfar; Van-Duong Dao; Jian Zhang; Muhammad Sultan Irshad; Calvyn T. Howells; et al. (Chemical Engineering Journal, 2025)

Environmentally friendly detoxification of pistachios from aflatoxins using citric acid and Glycine-based bio-MOF - Danfeng He; Ruijing Cheng; Xiaolin Zhang; Xu Han; Fujiang Zhou (Food Chemistry, 2025)

Tough, antibacterial, and antioxidant chitosan-based composite films enhanced with proanthocyanidin and carvacrol essential oil for fruit preservation - Lijun Qian; Ruijing Jia; Quanling Zhao; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Shuduan Deng; Zhiyong Qin (Food Research International, 2025)

Analysis of ionospheric TEC response to solar and geomagnetic activities at different solar activity stages - Jiandi Feng; Yibin Zhang; Wang Li; Baomin Han; Zhenzhen Zhao; Ting Zhang; Ruijing Huang (Advances in Space Research, 2023)

Growth and physiological–biochemical characteristics of cucumber (Cucumis sativus L.) in the presence of different microplastics - Haoran Zhuang; Xiaoyi Liu; Han Ma; Ruijing Li; Bo Liu; Ziyu Lin; Zhenxia Li (Arabian Journal of Geosciences, 2023)

RNase1 can modulate gut microbiota and metabolome after Aeromonas hydrophila infection in blunt snout bream - Ruijing Geng; Han Liu; Kianann Tan; Zhiqiang Wang; Weimin Wang (Environmental Microbiology, 2021)
Summary Pancreatic ribonuclease (RNase1) of Megalobrama amblycephala exhibits both antimicrobial and digestive activity. The gut microbiome improve the digestion and metabolic capacity and enhance the functioning of the immune system of the host against pathogenic bacteria. In this study, we aimed to assess the protective effect of RNase1 on Aeromonas hydrophila‐ induced inflammation and intestinal microbial metabolism. Megalobrama amblycephala were randomly divided into three groups: control (injected PBS), infection ( A. hydrophila‐ injected), and treatment group (RNase1 pretreatment 24 h before the A. hydrophila injection). The morphological symptoms were significantly alleviated by RNase1. RNase1 reshaped the perturbed gut microbiota by upregulating Proteobacteria and Vibrio richness and downregulating Firmicutes, Chlamydiae, Bacillus , and Gemmobacter richness. The lysophosphatidylcholine, (±) 17 HETE, D‐ (+) ‐cellobiose, and PC (20:5) in the treatment group were restored by RNase 1 protein treatment to the level of the control group. In the treatment group, phospholipid metabolism, fatty acid metabolism, glucose metabolism and lipid metabolism were different from the control and infection groups. The proinflammatory factors concentration in intestinal samples significantly increased after A. hydrophila infection. Our results revealed that RNase1 plays an important role in resistance to pathogen invasion, reducing inflammation, and improving intestinal function, thus inhibiting the occurrence of disease.